ANALYSIS OF THE INFLUENCE OF LOCATION, PRICE AND QUALITY OF SERVICE ON CONSUMER PURCHASE DECISIONS - Milka Rositi Sianipar; David Arjuna Situmorang; Putri Dian Sari Harefa; Okta Sari Rajagukguk; Nurma Junita Sidauruk; Januardin Januardin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the effect of examination area, cost, and nature of the administration on the purchase choice of buyers at PT. Coronavirus Parade during the pandemic. The strategy used in this study is a quantitative methodology. Using the SPSS program to collect test information and test measurable investigations. H Result area of ​​this research variable Positive massive impact on critical purchase choices 0.008 <0.05 and t count 2.710. The cost factor affects the choice of buying, with 0.03 < 0.05 and the significance of t –count 2.735 The nature of the administrative factor greatly influences the choice of buying, with a critical increase of 0.000 <0.05 and t count 3.737 Factors of area, cost, and the nature of the administration affect concurrent purchase option